Light emitting diodes containing Langmuir-Blodgett films of copolymer of a poly(p-phenylene-vinylene) derivative and poly(octaneoxide) - Olivati, Clarissa A. [UNESP]; Peres, Laura O.; Wang, Shu H.; Giacometti, Jose A.; Oliveira, Osvaldo N.; Balogh, Debora T. (Amer Scientific Publishers, 2008)
The properties of Langmuir and Langmuir-Blodgett (LB) films from a block copolymer with polyethylene oxide and phenylene-vinylene moieties are reported. The LB films were successfully transferred onto several types of substrates, with sufficient quality to allow for evaporation of a metallic electrode on top of the LB films to produce polymer light emitting diodes (PLEDs). The photoluminescence and electroluminescence spectra of the LB film and device were similar, featuring an emission at ca. 475 nm, from which we could infer that the emission mechanisms are essentially the same as in poly(p-phenylene) derivatives. Analogously to other PLEDs the current versus voltage characteristics of the LB-based device could be explained with the Arkhipov model according to which charge transport occurs among localized sites. The implications for nanotechnology of the level of control that may be achieved with LB devices will also be discussed.
Keywords: polymer; Langmuir-Blodgett films; luminescence; electrical properties